IMPLEMENTASI PEMBELAJARAN BERBASIS PROJEK PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV DI SEKOLAH DASAR NEGERI IV TIGARAKSA - Novita Sari Sipayung, Kristin; Nurraeni, Yeni; Rosnaningsih, Asih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to find out what problems students encounter when carrying out project based learning in Indonesian language subjects in class 4 of SDN 4 Tigaraksa. This research uses qualitative descriptive. The subjects in this research were all 4th grade students at SDN 4 Tigaraksa. Data collection techniques use observation, interviews and documentation to find out what problems students encounter when carrying out project-based learning in Indonesian language subjects in class 4. The results of this research show that the majority of students can follow the learning well, even though there are some students are still having difficulties. Factors that support success include active student involvement, use of varied learning media, and intensive guidance from teachers. It can be concluded that project-based learning is proven to be able to improve students' skills in understanding and expressing poetry. Of the six students studied, three students were able to compose and recite poetry well, while the other three students still experienced difficulties.